Effect of Dexmedetomidine-Assisted Intravenous Anesthesia on Gastrointestinal Motility in Colon Cancer Patients After Open Colectomy - Ou, Chaopeng; Kang, Shiyang; Xue, Ruifeng; Lai, Jielan; Zhang, Yingjun (Frontiers in Surgery, 2022)
Background: To explore the effect of dexmedetomidine (Dex)-assisted intravenous anesthesia on gastrointestinal motility in colon cancer (CC) patients after open colectomy. Methods: A total of 102 CC patients undergoing open colectomy in our hospital from January 2018 to January 2020 were selected and randomly divided into observation group (n=51) and control group (n=51). The patients in control group received routine combined intravenous and inhalation anesthesia (CIIA), while those in observation group received Dex-assisted CIIA. The systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR) and mean arterial pressure (MAP) were compared at different time points between the two groups, and the intraoperative general conditions, dosage of anesthetics and recovery of gastrointestinal function were also compared between the two groups. Moreover, before operation and at 24 h after operation, the levels of serum gastrin (GAS) and plasma motilin (MTL) were detected by radioimmunoassay, and the level of plasma cholecystokinin (CCK) was detected by enzyme-linked immunosorbent assay. The incidence of gastrointestinal complications was recorded in both groups. Results: At T1-T3, HR, SBP, DBP and MAP level were lower in both groups than those at T0, and they were also lower in observation group than those in control group, showing significant differences (P<0.05). The dosage of propofol and remifentanil in observation group was lower than that in control group, and there was a significant difference (P<0.05). In observation group, the postoperative first exhaust time, first defecation time, first ambulation time and first feeding time were all earlier than those in control group, with significant differences (P<0.05). After operation, observation group had higher levels of GAS and MTL but a lower level of CCK than control group, and the differences were significant (P<0.05). The incidence rate of gastrointestinal complications in observation group (7.04%) was lower than that in control group (19.61%), and there was a significant difference (χ2=4.346, P<0.05). Conclusions: Dex-assisted intravenous anesthesia can facilitate the recovery of gastrointestinal motility, regulate the levels of gastrointestinal hormones, and stabilize the levels of hemodynamic indexes in CC patients after open colectomy.